ESSENCE, FORMS AND INSTRUMENTS OF AGRIBUSINESS STATE REGULATION - Sergey Mikchailovich Gorlov (Вестник Северо-Кавказского федерального университета)
It`s a wellknown fact, that the agribusiness development is based on interaction between the authority and economic structures. However the efficiency of such interaction depends on choosing the forms and instruments of agribusiness state regulation.